Protective Effect of Alcoholic Extract and Nanoparticles Extract of Prickly Pear Fruit against Thioacetamide-Induced Nephrotoxicity - Mohammed, Ali Nadhim; Obaid, Ashwaq Kadhem; Al-Salam, Heba A. Abd (American Journal of Biomedicine and Pharmacy, 2025)
Objective: this study was to evaluate the preventive impacts of alcoholic and nano extracts of cactus pear fruit (Opuntia ficus-indica) pulp and peel against thioacetamide (TAA)-induced renal toxicity and tissue damage in male albino rats. Methods: The study involved rats divided into six groups, each with six animals. The first group was given 0.9% NaCl alone for 14 weeks, while the second group received 200 mg/kg of thioacetamide (TAA) diluted in distilled water to induce renal toxicity. The third group received an alcoholic extract of prickly pear (pulp) at 100 mg/kg, followed by TAA administration. The fourth group received an alcoholic extract of prickly pear (peels) at 100 g/kg, followed by TAA administration. The fifth group received a nano-form extract (pulp) at 54 mg/kg, followed by TAA. The sixth group received a nano-form extract (peels) at 50 mg/kg followed by TAA till the conclusion of the study. Results: TAA exposure markedly raised renal function creatinine and urea and reduced the level of albumin and glomerular atrophy, widened Bowman’s space, caused destruction of renal tubule walls, detachment of their epithelial lining, congestion of blood vessels between renal tubules, destruction of renal tubule walls, and cellular necrosis. Treatment with alcoholic and nano extracts markedly decreased creatinine and urea levels and increased in the level of albumin and improvement in kidney tissue. Conclusion: These findings suggest that prickly pear fruit extracts demonstrate significant renal protective effects, potentially hindering the advancement of TAA-induced nephrotoxicity.